Bardet Biedl Syndrome: A Case Report (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: Bardet Biedl Syndrome; cromosome; ciliopathicDOI: 10.3329/jcmcta.v21i2.7738 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):44-46